
高数 不 定 积 分2
1个回答
展开全部
∫sinxln(tanx)dx
=-∫ln(tanx)d(cosx)
=-cosxln(tanx)+∫cosxd[ln(tanx)]
=-cosxln(tanx)+∫(cosx/tanx)d(tanx)
=-cosxln(tanx)+∫[(cosx)^2/sinx][1/(cosx)^2]dx
=-cosxln(tanx)+∫(1/sinx)dx
=-cosxln(tanx)+∫[sinx/(sinx)^2]dx
=-cosxln(tanx)-∫{1/[1-(cosx)^2]}d(cosx)
=-cosxln(tanx)-(1/2)∫{1-cosx+1+cosx)/[(1+cosx)(1-cosx)]}d(cosx)
=-cosxln(tanx)-(1/2)∫[1/(1+cosx)]d(cosx)
-(1/2)∫[1/(1-cosx)]d(cosx)
=-cosxln(tanx)-(1/2)ln(1+cosx)+(1/2)ln(1-cosx)+C
=-∫ln(tanx)d(cosx)
=-cosxln(tanx)+∫cosxd[ln(tanx)]
=-cosxln(tanx)+∫(cosx/tanx)d(tanx)
=-cosxln(tanx)+∫[(cosx)^2/sinx][1/(cosx)^2]dx
=-cosxln(tanx)+∫(1/sinx)dx
=-cosxln(tanx)+∫[sinx/(sinx)^2]dx
=-cosxln(tanx)-∫{1/[1-(cosx)^2]}d(cosx)
=-cosxln(tanx)-(1/2)∫{1-cosx+1+cosx)/[(1+cosx)(1-cosx)]}d(cosx)
=-cosxln(tanx)-(1/2)∫[1/(1+cosx)]d(cosx)
-(1/2)∫[1/(1-cosx)]d(cosx)
=-cosxln(tanx)-(1/2)ln(1+cosx)+(1/2)ln(1-cosx)+C
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询